Identification of mitochondria-related key gene and association with immune cells infiltration in intervertebral disc degeneration - Guo, Wei; Mu, Kun; Li, Wen-Shuai; Gao, Shun-Xing; Wang, Lin-Feng; Li, Xiao-Ming; Zhao, Jian-Yong (Frontiers in Genetics, 2023)
Intervertebral disc (IVD) degeneration and its inflammatory microenvironment ultimately lead to discogenic pain, which is thought to originate in the nucleus pulposus (NP). Increasing evidence suggests that mitochondrial related genes are strictly connected to cell functionality and, importantly, it can regulate cell immune activity in response to damaged associated signals. Therefore, identification of mitochondria related genes might provide novel diagnostic markers and therapeutic targets for IVD degeneration. In this study, key genes involved in NP tissue immune infiltration in IVD degeneration were identified by bioinformatic analysis. Weighted gene co-expression network analysis (WCGNA) was used to screen the key modules. Random forest analysis was applied to identify the signature genes. Then gene set enrichment analysis (GSEA) was exerted to explore the signaling pathways related to the signature genes. And the immune cells infiltration was subsequently classified via using CIBERSORT. Function of the hub gene was confirmed by PCR, western blotting and ELISA. Finally, we identified MFN2 as a crucial role in the process of NP cell pyroptosis and NLRP3 inflammasome activation. We speculate that the overexpressed MFN2 in NP tissue along with the infiltration of CD8+ T cells, NK cell and neutrophils play important roles in the pathogenesis of IVD degeneration.